Quelques hommes « extra-ordinaires » du début de l’ère Meiji - Christian Galan (Les Cahiers de Framespa, 2012)
The implementation of a modern education system constituted one of the main elements of the modernization of Meiji era’s Japan, both in terms of issues and human and material investments. As the model chosen by Japanese was western and plural, its setting up required young intellectuals to get involved in the study of American and European languages, knowledge, and methods.The little-studied question of the intellectual and human cost of this modernization appears to manifest itself particularly in the profiles of the generations of Western studies (yogaku) specialists born between 1830 and 1840, that is to say, those who had also been the most directly involved in the transition process between old and modern Japan.The exceptional intellectual, psychological, and physical effort these young men had to supply seems – except for Fukuzawa Yukichi – to have indeed shortened their young lives. A common point they share, along with their social origin in the low-ranking samurai class, was their undertaking of double course of studies and/or travels overseas. Even if it is difficult to conclude that this relationship would be cause and effect and that one should balance conclusions with respects to their degree of involvement (whether local or national) in the modernization process, it appears clear that Western studies specialists of these years paid a heavier toll than the other actors in the modernization process, particularly their classical studies counterparts.